Intramolecular Oxa-Michael Cyclization of 2’-Hydroxychalcones for the Synthesis of Flavanones: A Comparative Study - Ramadhini, Rizky Annisa; Danova, Ade; Roswanda, Robby (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2025)
In this study, flavanones were synthesized using a two-step reaction process starting from 2’ hydroxyacetophenone and aldehydes. Claisen-Schmidt condensations were carried out on the starting materials to produce 2’-hydroxychalcones with mono-, di-, and tri-substituents on ring B. Subsequently, flavanones were produced via intramolecular oxa-Michael cyclization under three different reaction conditions: methanesulfonic acid in ethanol, sodium acetate in methanol, and piperidine in water. These approaches aimed to investigate the steric and electronic effects to achieve high yields in optimal reaction conditions for flavanone synthesis. Twelve 2’-hydroxychalcones (1a-1l) were successfully synthesized with yields ranging from 17% to 99%. The use of methanesulfonic acid in ethanol resulted in modest flavanone yields (11% for 2a, 13% for 2c). The synthesis of flavanones using sodium acetate was successful for seven 2’-hydroxychalcones (2a-2g), yielding products with varying yields (2-49%). Furthermore, piperidine was effective for three 2’-hydroxychalcones (1a, 1b, 1e), resulting in high flavanone yields (74-93%). These findings indicate that the three reaction conditions are only effective for certain 2’-hydroxychalcones.